Spectral Features and Charge Dynamics of Lead Halide Perovskites: Origins and Interpretations - Sum, Tze Chien (2016)
Lead halide perovskite solar cells are presently the forerunner among the third generation solution-processed photovoltaic technologies. With efficiencies exceeding 20% and low production costs, they are prime candidates for commercialization. Critical insights into their light harvesting, charge transport, and loss mechanisms have been gained through time-resolved optical probes such as femtosecond transient absorption spectroscopy (fs-TAS), transient photoluminescence spectroscopy, and time-resolved terahertz spectroscopy. Specifically, the discoveries of long balanced electron–hole diffusion lengths and gain properties in halide perovskites underpin their significant roles in uncovering structure–function relations and providing essential feedback for materials development and device optimization. In particular, fs-TAS is becoming increasingly popular in perovskite characterization studies, with commercial one-box pump–probe systems readily available as part of a researcher’s toolkit. Although TAS is a powerful probe in the study of charge dynamics and recombination mechanisms, its instrumentation and data interpretation can be daunting even for experienced researchers. This issue is exacerbated by the sensitive nature of halide perovskites where the kinetics are especially susceptible to pump fluence, sample preparation and handling and even degradation effects that could lead to disparate conclusions. Nonetheless, with end-users having a clear understanding of TAS’s capabilities, subtleties, and limitations, cutting-edge work with deep insights can still be performed using commercial setups as has been the trend for ubiquitous spectroscopy instruments like absorption, fluorescence, and transient photoluminescence spectrometers.